การปรับงานระดับกลุ่ม การปรับงานรายบุคคล และความผูกใจมั่นในงานระดับบุคคล: การวิเคราะห์อิทธิพลส่งผ่านแบบเหลื่อมเวลาไขว้ - ติณณ์ ชุ่มใจ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study aims to examine the causal relationship between collective job crafting, individual job crafting and individual work engagement in the sample of Thailand public company’s monthly employees. This study was divided to 2 parts which included cross-sectional study and cross-lagged panel design with the data collection period of 1 week-gap 3 times (N = 175). The result in cross-sectional study found that the model of collective job crafting, individual job crafting and individual work engagement was fitted to empirical data well and had positive direct effect with statistically significant. The individual job crafting was found as a mediator between collective job crafting and individual work engagement with significant at three different points of time but there was no significant direct effect path from collective job crafting to individual work engagement. The cross-lagged panel design found no significant positive direct paths, except for T1 collective job crafting to T2 Individual job crafting.